Use of extracorporeal membrane oxygenation in non-elective major thoracic surgery for infectious lung abscess. (25th February 2022) - Schweigert, Michael; Dubecz, Attila; Giraldo Ospina, Carlos F; Spieth, Peter; Almeida, Ana Beatriz; Richter, Torsten; Witzigmann, Helmut; Stein, Hubert J
Abstract: OBJECTIVES: Extracorporeal membrane oxygenation (ECMO) support for elective cardiothoracic surgery is well established. In contrast, there are not much data regarding the usefulness and outcome of ECMO in non-elective major lung resections for infectious lung abscess. METHODS: All patients undergoing non-elective major lung surgery for infectious lung abscess at 5 centres in Germany, UK and Spain were enrolled in a prospective database. Malignant disorders and intrathoracic complications of other procedures were excluded. RESULTS: There were 127 patients. The median age was 59 years (interquartile range 18.75). The mean Charlson index of comorbidity was 2.83 (standard deviation 2.57). Surgical procedures were lobectomy (89), pneumectomy (20) and segmentectomy (18). ECMO was used for 10 patients (pneumectomy 2, lobectomy 8) and several more received pre-ECMO treatment. Mortality was 17/127. Intraoperatively no ECMO-associated complications were encountered. EMCO [1/10 vs 16/117; odds ratio (OR): 0.70, 95% confidence interval (CI) 0.08–5.91, P = 0.74] and the extent of pulmonary resection were not associated with higher mortality. Preoperative sepsis (OR: 17.84, 95% CI 2.29–139.28, P < 0.01), preoperative air leak (OR: 13.12, 95% CI 4.10–42.07, P < 0.001), acute renal failure (OR: 7.00, 95% CI 2.19–22.43, P < 0.01) and Charlson index of comorbidity ≥ 3 (OR: 10.83, 95% CI 2.36–49.71, P < 0.01) were associated with significantly higher mortality. CONCLUSIONS: The application of ECMO is widening the possibilities for successful surgical management of infectious, non-malignant lung abscesses. Particularly, patients with marginal functional operability benefit from the availability and readiness to use ECMO. Mortality is determined by the burden of pre-existent comorbidity, severe sepsis and septic shock. Abstract : During the last 2 decades, extracorporeal membrane oxygenation (ECMO) has become an important tool in elective general thoracic surgery [1].